Enhancing Indonesian National Police Penal Mediation Through Conflict Mediator Certification for Bhabinkamtibmas - Muhammad Akbar Magistra Putra (Sekolah Tinggi Ilmu Kepolisian, 2024)
This research seeks weaknesses in the internal police regulations concerning the duties of Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat (Bhabinkamtibmas). There was a conflict in the duties of the Bhabinkamtibmas, which is tasked with maintaining the security of public safety (Harkamtibmas), but can also carry out criminal investigation duties, penal mediation. Penal mediation embodies the concept of restorative justice which has been implemented by the Indonesian National Police (INP) through the role of Bhabinkamtibmas. Doctrinal study is being used in this research, where it used documents found regarding the problem. The document analysis is conducted toward documents informing the implementation of conflict mediator certification for Bhabinkamtibmas in case of horizontal conflict resolution, such as related internal police regulations. From documents analyzed, it was found that there has been an absence of regulation in place for Bhabinkamtibmas regarding penal mediation mechanism. Apart from their main duty ensuring public safety, Bhabinkamtibmas is expected to support the INP in carrying out their functions, including criminal investigations to resolve cases outside court. Practically, there have been some problems with horizontal conflict management by Bhabinkamtibmas. Based on this, the author initiated to certify conflict mediators within the Bhabinkamtibmas to enhance the effectiveness of INP penal mediation.